PENGARUH ASIMETRI INFORMASI TERHADAP PRAKTIK MANAJEMEN LABA - Agus Defri Yando (LPPM Universitas Putera Batam, 2018)
This study aims to examine and analyze the effect of asymmetry of information to earnings management practices. The population in this research is manufacturing companies listed in Indonesia Stock Exchange (BEI) in 2011-2016. The technique in this study using purposive sampling method using predetermined criteria of the obtained sample of 41 companies. Tests using simple linear regression model. The results showed that the asymmetry of information effect on earnings management practices.